United States : Report on the Observance of Standards and Codes; FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This report provides a summary of the Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT) measures in place in the United States on May 2006. The report describes and analyzes those measures and provides recommendations on how certain aspects of the system could be strengthened. The views expressed in this document are the views of the Financial Action Task Force (FATF), but do not necessarily reflect the views of the Boards of the IMF or World Bank. The Bank Secrecy Act provides the basis for most of the preventive measures applied to the financial sector and other businesses.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet